Mensuração do grau de inovação em micro e pequenas empresas do estado de Sergipe - Silva Néto, Ana Teresa da (2012)
There is consensus among academic and business (SMEs) communities about the importance of innovation as a success factor for enterprises competition and survival. In Brazil, despite the micro and small businesses represent 99% of existing businesses and be responsible for generating the most jobs, has been verified in several studies, the small innovative content of these companies. The main objective of this study was to measure the degree of innovation of micro and small enterprises in Sergipe State. To achieve this goal it was accomplished a survey with 1,260 SMEs participants of the local innovation agents (ALI) project of SEBRAE in Sergipe, between companies of the chains of food, construction, wood and furniture, health and textile. This search can be considered as descriptive and quantitative once sought to produce quantitative descriptions on micro and small enterprises from Sergipe and measure its degree of innovation. It was longitudinal, because the data were collected in two steps: the first were collected data of all companies participating in the project ALI there and in the second step we collected data from 560 companies that concluded the work plan; to verify if there have been changes in the degree of innovation of the companies after the intervention of the project. The tool used to measure the degree of innovation was based on the innovation radar, developed by Sawhney, Wolcott and Arroniz (2006), which uses twelve dimensions: offer, brand, platform, solutions, customers, relationships, adding value, processes, organization, supply chain, presence and network, by which a company can seek ways to innovate. This tool was complemented by Bachmann and Destefani (2008) with an innovative ambience dimension, because it is considered a prerequisite that an organizational climate favor innovation. As a result it is worth noting that in the first stage of the study, the average level of innovation found in SMEs in Sergipe was 2.01 and, in the second step, was 2.10, on a scale ranging from 1 to 5. These data indicate that innovation is still incipient in these group of companies and, therefore, the companies were classified as low innovative.